An investigation into electron scattering from pyrazine at intermediate and high energies - Sanz, A. G. (2018)
This work is partially supported by the Spanish Ministerio de Economia y Competitividad (Projects FIS2009-10245 and FIS2012-31320) and the EU/ESF COST Action MP1002 "Nanoscale Insights into Ion Beam Cancer Therapy (Nano-IBCT)". M. C. F. is financially supported by the Comunidad Autonoma de Madrid local government. This work was also supported by the EPSRC and the Australian Research Council through its Centres of Excellence programme. We acknowledge Professor Carl Winstead for providing us with numerical values of their data presented in this paper. D. A. and F. F. S. acknowledge the Portuguese Foundation for Science and Technology (FCT-MEC) for a post-graduate SFRH/BD/61645/2009 and post-doctoral SFRH/BPD/68979/2010 grants. We are also grateful to the partial funding from the Portuguese research Grant Nos. PEst-OE/FIS/UI0068/2011 and PTDC/FIS-ATO/1832/2012 through FCT-MEC. P. L.-V. acknowledges his visiting Professor position at The Open University, UK.